Environmental temporal determinants of community variability using natural aquatic microcosms - Therriault, Wayne Thomas (My University, 2000)
Histories, biotic factors, and abiotic factors interact to determine biodiversity. These factors also influence community composition, community structure, and community constancy (persistence) over time. By examining multiple communities from a common species pool in a system that spans a range of physical conditions, it may be possible to determine the role environmental variables play in forming and maintaining community composition and structure, especially over time. Species richness and diversity were determined by abiotic pool conditions such that the observed community consisted of tolerant species that accumulated over time. These abiotic variables also can be used to represent habitat heterogeneity. I showed that increased habitat heterogeneity promoted increased biodiversity, which, in turn, further increased biodiversity by self-generation of heterogeneity. Frequency of pool desiccation was another abiotic variable considered and it was found that diversity, richness, and abundance all decreased with increased frequency of desiccation while compositional stability decreased. Temporary pools were shown to have a similar "type" of community structure; one dominated by a few species with good dispersal and colonization abilities. One abiotic variable, pool salinity, was found to most strongly influence community composition and structure. For example, freshwater pools were dominated by ostracods and insects while brackish water pools were dominated by copepods. As salinity increased, ostracod abundances decreased while copepod abundances increased. As expected, community constancy was greatest over short temporal intervals. Environmental variability reduced community constancy. Pool temperature was shown to affect species abundances but pool salinity determined the community composition. Increased environmental variability (based on temporal changes in physicochemical variables) also resulted in increased community and population variability with community structure being more variable in unstable habitats. In conclusion, much of the results indicate that communities respond independently and asynchronously to environmental variables.
Keywords: Biology; Biology